2020
DOI: 10.18410/jebmh/2020/532
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Pranayama for Improvement of Pulmonary Function Tests (PFT) in Post Coronary Artery Bypass Grafting (CABG) Surgery Patients

Abstract: BACKGROUND Incidence of Coronary Artery Disease (CAD) is increasing day by day. Cardiac rehabilitation is an important aspect of management of Coronary Artery Disease. Anuloma Viloma Pranayama is beneficial to cardiac patients as it increases parasympathetic activity and lowers blood pressure and respiratory rate. This study was designed to assess the benefit of Anuloma Viloma Pranayama as rehabilitation therapy in post Coronary Artery Bypass Grafting (CABG) surgery patients. Parameters of pulmonary function t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Pulmonary function test showed improvement in the intervention group; correlation is found with our results. [20] In their research work, Jadhav KG found that chair aerobics improves exercise tolerance and functional capacity in post-CABG patients. The 6-minute walk test showed improvement.…”
Section: Discussionmentioning
confidence: 98%
“…Pulmonary function test showed improvement in the intervention group; correlation is found with our results. [20] In their research work, Jadhav KG found that chair aerobics improves exercise tolerance and functional capacity in post-CABG patients. The 6-minute walk test showed improvement.…”
Section: Discussionmentioning
confidence: 98%
“…Pulmonary function test showed improvement in the intervention group; correlation is found with our results. 20 In their research work, that chair aerobics improves exercise tolerance and functional capacity in post-CABG patients. The 6-min walk test showed improvement.…”
Section: Discussionmentioning
confidence: 99%